Weibull, Gamma atau Eksponensial sebagai Sebaran Peluang Masa Inkubasi HIV untuk Pendugaan Infeksi HIV dengan Algoritma EM - Herlina Hanum (Jurnal Penelitian Sains, 2002)
This paper was summarised from two research carried out by the author. The aim was to analyze and determine the probability distribution of HIV incubation period so it can be used for estimation of HIV infection cases with EM Algorithm. The distribution was determined through the analysis of EM Algorithm resistance against the change of Weibull and Gamma parameters. Exponential distribution is a special form of Weibull and Gamma dirtribudons. In conclusion, the best distribution of HIV incubation period to use with EM Algorithm is Exponential distribution.